Sanhuang Decoction Controls Tumor Microenvironment by Ameliorating Chronic Stress in Breast Cancer: A Report of Ninety Cases - Feng, Ming; Wang, Huanhuan; Zhu, Zhiyuan; Yao, Bowen; Li, Yongfei; Xue, Jingxian; Cao, Sihan; Shao, Xinyi; Xu, Yanlei; Sohn, Ki Cheul; Shin, Im Hee; Yao, Chang (Frontiers in Oncology, 2021)
Background: Long term endocrine treatment with deprivation of one’s estrogen would result in chronic stress with a series of uncomfortable symptoms leading not only to the decrease of quality of life, but also even induce the recurrence of cancer, which may be mediated primarily through enhanced expression of angiogenic factors as well as a series of inflammatory microenvironmental changes which favor to tumor progress. Methods: 90 patients who met the inclusion/exclusion criteria were allocated to treatment group or control group randomly. The modified scores of Kupperman，as well as those of anxiety scale (SAS) and depress scale (SDS) for the quality of life were evaluated per month. The body microenvironment plasma indices related to the chronic stress as for oxidative and antioxidative stress markers, inflammatory factors, hemorheology, coagulation, lipid and D-dimer, immunologic functions as well as tumor biomarkers and angiogenic factor of VEGF were measured before and after treatment. In addition, patients’ serum after treatment for 3 months and 6 months were cultivated with tamoxifen resistant MCF-7 cells to detect their growth rate. Results: After treatment for 5 months, the scores in the treatment group decreased to the level of nearly normal life as compared to the conditions in the control group without significant improvement. After treatment for 6 months, all the indices related to body microenvironment as well as the tumor biomarkers of CEA and CA153 and the angiogenic factor of VEGF were detected to be significant modified to the normal levels in the treatment group. Accordingly, the patients’ serum in the treatment group was shown to significantly inhibit the growth of tamoxifen resistant MCF-7 cells after treatment for 3 months and 6 months. Conclusions: Our primary research showed that treatment with Chinese medicine SHD could effectively improve the quality of life and change the body microenvironment to favor the control of tumor growth or drug resistance.